CONCEPTION RATE AND LITTER SIZE IN BITCHES AFTER TRANSCERVICAL INSEMINATION WITH FRESH AND FROZEN SEMEN - SATHIAMOORTHY, T; ASOKAN, S A; VEERAPANDIAN, C (The Indian Journal of Animal Reproduction, 2023)
Study was conducted to compare conception rate and litter size in bitches inseminated followingTranscervical route with fresh and frozen semen. Twenty bitches of different breeds were equallydivided into two groups viz., Group I and II each. Semen collected from respective male dogs of differentbreeds was evaluated and cryopreserved with Tris egg yolk extender. All the bitches in both the groupswere subjected to vaginal exfoliative cytology and vaginoscopy from day 5 of proestrus to determine thetime of insemination. Artificial insemination was performed in bitches using the endoscopic transcervicaltechnique in Group I and II with fresh and frozen semen, respectively. The conception rate was 50.00 and 30.00 per cent in group I and 11, respectively. The litter size obtained in group I and II was 6.25 ± 0.10 and 3.00 ± 1.00 respectively with a range of 6 to 8 and 2 to 5. Hence, it is concluded from the study that the conception rate and litter size in bitches was higher for fresh semen compared to frozen semen following transcervical insemination technique.
Keywords: Endoscopic Transcervical insemination; Bitches; Conception rate